1989
DOI: 10.1002/cne.902800106
|View full text |Cite
|
Sign up to set email alerts
|

Neurons of origin and fiber trajectory of amygdalofugal projections to the medial preoptic area in syrian hamsters

Abstract: The amygdaloid neurons of origin and the trajectory of amygdaloid fibers to the medial preoptic area of the adult male Syrian hamster were identified by using horseradish peroxidase (HRP) histochemistry. After iontophoresis of HRP into the medial preoptic area, retrogradely labeled amygdaloid neurons were located in the dorsal and caudal parts of the medial amygdaloid nucleus and throughout the amygdalohippocampal area. No amygdaloid neurons were labeled after HRP applications confined to the most rostral port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…In rats, the area lateral to the medial MPN (i.e, the lateral MPN) was labeled much less than the medial MPN after Pha-L injections that filled the MeApd (Canteras et al, 1995). Projections to the PdPN were not mentioned in studies of MeApd outputs in rats or hamsters but are suggested by the density of labeled fibers shown in the POA (Gomez and Newman, 1992;Canteras et al, 1995;Coolen and Wood, 1998) just rostral and caudal to where the PdPN is located (Maragos et al, 1989;Swanson, 1992) after tracer injections in the MeApd.…”
Section: Pdpn and Lateral Meapd Efferents And Afferentsmentioning
confidence: 91%
“…In rats, the area lateral to the medial MPN (i.e, the lateral MPN) was labeled much less than the medial MPN after Pha-L injections that filled the MeApd (Canteras et al, 1995). Projections to the PdPN were not mentioned in studies of MeApd outputs in rats or hamsters but are suggested by the density of labeled fibers shown in the POA (Gomez and Newman, 1992;Canteras et al, 1995;Coolen and Wood, 1998) just rostral and caudal to where the PdPN is located (Maragos et al, 1989;Swanson, 1992) after tracer injections in the MeApd.…”
Section: Pdpn and Lateral Meapd Efferents And Afferentsmentioning
confidence: 91%
“…In preliminary studies, channel responses to opioids were not observed on the smaller cells (not shown), and so only the larger cells were used here. The AHA is known to be a densely packed cell layer made up of 30-to 40-m pyramidal or spindle-shaped projection neurons, whereas the other regions of the amygdala that are directly ventral to the AHA and thus are also included in our preparation comprise smaller neurons and glia (17). Consequently, we recorded principally from AHA projection neurons.…”
Section: Methodsmentioning
confidence: 99%
“…The medial amygdala receives projections from the main and accessory olfactory bulbs (Davis et al, 1978; Lehman and Winans, 1982), and sends its projections to the mPOA and bed nucleus of the stria terminalis (Gomez and Newman, 1992; Kevetter and Winans, 1981; Maragos et al, 1989). B6D2F1 hybrid maters retain the ability to discriminate between female and male mice while non-maters have lost this ability (Park et al, 2009), and this finding further supports the hypothesis that the neural circuitry connecting the MPOA to the olfactory system that governs male sexual behavior may remain intact in the maters but not in the non-maters.…”
Section: Discussionmentioning
confidence: 99%